Working conditions of agricultural workers on mixing plant areas of foundry shops - A. M. Lazarenkov; M. A. Sadokha (Литьë и металлургия)
The working conditions of agricultural workers on mixing plant areas are examined, including the production factors that determine these conditions. The results of research on the parameters of the working conditions for agricultural workers are compared with the regulatory values. It has been established that a comprehensive assessment of the working conditions of agricultural workers should take into account the duration of exposure to the working equipment, the equipment and manual tools used, and the nature of the production.